The B2B social media book : become a marketing superstar by generating leads with blogging, Linkedln, Twitter, Facebook, e-mail, and more - Bodnar, Kipp, 1982-; Cohen, Jeffrey L., 1965- (Wiley, 2012)
"Advance your B2B marketing plans with proven social media strategiesLearn social media's specific application to B2B companies and how it can be leveraged to drive leads and revenue. B2B marketers are undervalued and under appreciated in many companies. Social media and online marketing provide the right mix of rich data and reduction in marketing expenses to help transform a marketer into a superstar. The B2B Social Media Book provides B2B marketers with actionable advice on leveraging blogging, LinkedIn, Twitter, Facebook and more, combined with key strategic imperatives that serve as the backbone of effective B2B social media strategies.This book serves as the definitive reference for B2B marketers looking to master social media and take their career to the next level. Describes a methodology for generating leads using social media Details how to create content offers that increase conversion rates and drive leads from social media Offers practical advice for incorporating mobile strategies into the marketing mix Provides a step-by-step process for measuring the return on investment of B2B social media strategies The B2B Social Media Book will help readers establish a strong social media marketing strategy to generate more leads, become a marketing superstar in the eye of company leaders, and most importantly, contribute to business growth"--Resumé vydavatele
Keywords: internetový marketing; internetové sociální sítě -- ekonomické aspekty; sociální média -- ekonomické aspekty; Internet marketing; Internet social networks -- economic aspects; social media -- economic aspects; příručky; handbooks, manuals, etc